Ethnomedicinal study of medicinal plants used by the Melanau Igan community of Sarawak - Rajoo, Keeren Sundara; Umayrah, Nurul Azwany; Lepun, Philip (Ilia State University, Institute of Botany, Department of Ethnobotany, 2024)
Abstract Background: The Melanau Igan community is a distinctive subgroup of the larger Melanau ethnic group. What sets the Melanau Igan apart from other Melanau communities is their unique dialect and cultural characteristics. The present study was conducted to document the herbal medicinal plants used by this community, and the cultural, geographical, and historical dimensions that shape this ethnomedicinal system. Methods: A total of 71 respondents from five Melanau Igan villages were interviewed in this study. The results were evaluated based on the plant’s total use-reports, number of respondents citing the plant, and use-reports by ailment category. Moreover, the similarity with other neighboring ethnic groups were calculated. Results: The 71 respondents in this study cited 72 plant species with a total of 596 use reports. Fever, headaches, skin issues, diabetes, and hypertension are the most common ailments treated with traditional medicine in the Melanau Igan community. Hibiscus rosa-sinensis, Citrus aurantifolia, Psidium guajava, Ageratum conyzoides and Citrus limon play prominent roles in the traditional medicine of the community, being the top five plants with the most respondent citations. Conclusions: A distinctive feature of the Melanau Igan community's ethnomedicine is the significant role of women in traditional healing due to their household and caregiving responsibilities. The uniqueness of the community’s traditional medicine is influenced by historical and cultural factors, while geographical proximity does not guarantee similarity. Their coastal lifestyle, historical associations, and cultural ties with Malays shape their ethnomedicinal practices, underscoring the importance of considering these contexts when studying traditional medicine in Borneo.